STUDY REGARDING THE LEVEL OF SPATIAL ORIENTATION IN PHYSICAL EDUCATION STUDENTS DURING THE SKIING COURSE - Silviu-Ioan PAVEL; Gloria RAŢĂ (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
Behavioral orientation is the process by which the body 's ability to properly locate in time and space systems own body and the surrounding world in order to achieve voite.Ca action in achieving this goal we proposed evaluation research and knowledge level , orientation in space of the students from physical education before starting the educational process skiing discipline . Research subjects are represented by first year students of the same faculty , students specializations and Sport Physical education and sports and motor performance . Following the completion of this test it was found that registered high score indicates better performance and increased people tested their ability to work simultaneously with multiple types of information and tasks that require evaluation , while more choice.